Prevalence of Obesity in Preschool Children at Hilla/Babylon/Iraq 2020 - Bahaa Mufeed Kadhim (Wolters Kluwer Medknow Publications, 2024)
Background: More and more preschool children in Iraq and elsewhere are becoming overweight or obese. Many countries are now reporting a similar trend among preschool children. However, little information is available on the prevalence of overweight and obesity among preschool children in Iraq. In addition, available data are based on reported rather than measured height, weight, and body mass index (BMI). Aims: The aim of the study was to determine the prevalence of obesity/overweight among preschool children in private and governmental kindergartens (KGs) at Hilla 2020. Settings and Design: This study was a cross-sectional study. Materials and Methods: In order to determine the prevalence of obesity in preschool children 2-5 year old children who are attending kindergartens are selected as a sample in a cross sectional manner, the researcher measured the height and weight and calculated the BMI for each child to compare it with the WHO growth charts. The study was conducted for a period extended from January 2020 to December 2020. The total participants were 2148 parents and their 2-5-year-old children selected from all KGs available. The data were collected using an adapted questionnaire and were analyzed electronically. Statistical Analysis: Analysis of data was carried out using the available statistical package of SPSS-27 (Statistical Package for the Social Sciences, version 27). Data were presented in simple measures of frequency, percentage, mean, standard deviation, and range (minimum-maximum values). The significance of difference of different percentages (qualitative data) was tested using the Pearson Chi-square test. Statistical significance was considered whenever P ≤ 0.05. Results: The prevalence of overweight and obesity in preschool KG children was 14.8% and 5.9%, respectively; the main factors that affect childhood obesity are family income and the presence of obesity in other family members. Conclusions: There is a high prevalence of obesity/overweight among 2-5-year-old children with a significant difference regarding obesity/overweight prevalence between governmental and private KGs.